2013
DOI: 10.1590/s1982-56762013005000020
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of Corynespora cassiicola from soybean to carbendazim and prothioconazole

Abstract: The incidence of target spot disease on soybean has increased in recent years in Brazil even with intensive use of fungicides, and fungal resistance has been reported in recent studies. The objective of this study was to determine the fungicide sensitivity to carbendazim and prothioconazole in a sample of 24 isolates of Corynespora cassiicola from soybean collected from 1996 to 2011 in the states of Paraná, Mato Grosso and São Paulo (Brazil) and Corpus Christi (Paraguay). The 50% effective concentration (EC 50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(47 citation statements)
references
References 10 publications
(11 reference statements)
1
42
1
3
Order By: Relevance
“…Most isolates had EC 50 values above the highest tested concentration (1000 µg mL -1 ), indicating resistance of C. cassiicola to carbendazim and thiophanate-methyl in Brazil. Similar results were obtained in other studies (26,31,33).…”
Section: Effect Of Fungicides On Target Spot Progress Under Field Consupporting
confidence: 93%
See 1 more Smart Citation
“…Most isolates had EC 50 values above the highest tested concentration (1000 µg mL -1 ), indicating resistance of C. cassiicola to carbendazim and thiophanate-methyl in Brazil. Similar results were obtained in other studies (26,31,33).…”
Section: Effect Of Fungicides On Target Spot Progress Under Field Consupporting
confidence: 93%
“…In a recent survey, there was evidence of sensitivity of C. cassiicola to carbendazim only in samples collected before 2007, and nonsensitivity in recent isolates obtained after 2008 (33). These authors considered isolates sensitive when EC 50 ≤ 1.0 µg mL -1 , and highly resistant when EC 50 ≥ 50 µg mL -1 .…”
Section: Effect Of Fungicides On Target Spot Progress Under Field Conmentioning
confidence: 99%
“…The results suggested that (R,R)-Whelk-O1 could not separate whether prothioconazole or prothioconazole-desthio, while Chiralcel OD showed the best resolution capability (see Table S1). The maximum Rs could be up to 24 The steric hindrance adjacent to the chiral carbon played an important role in the resolution on (R,R)-Whelk-O1. It was hard to realize the chiral separation of prothioconazole only on Chiracel OJ-H and Chiralcel OD (see Table 1).…”
Section: Chiral Separations Under Normal Phasementioning
confidence: 99%
“…The per cent inhibition of radial growth, sporulation and spore germination over control was calculated as per the following formula (Vincent, 1977 Xavier et al, (2013), studied the incidence of target spot disease on soybean has increased in recent years in Brazil even with intensive use of fungicides, and fungal resistance has been reported in recent studies. They determine the fungicide sensitivity to carbendazim and prothioconazole in a sample of 24 isolates of C. cassiicola from soybean collected from 1996 to 2011 in the states of Parana Mato Grosso and Sao Paulo (Brazil) and Corpus Christi (Paraguay).…”
Section: In Vitro Evaluation Of Fungicidesmentioning
confidence: 99%